2016
DOI: 10.3126/jnps.v36i2.14985
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Serum Neutrophil Gelatinase Associated Lipocalin(NGAL) as an Early Marker of Acute Kidney Injury in Asphyxiated Neonates

Abstract: Introduction: Acute Kidney Injury (AKI) is a common

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Among them, 34 studies ( 10 , 11 , 16 18 , 20 22 , 24 , 27 29 , 31 34 , 39 , 42 45 , 47 , 48 , 52 , 53 , 55 – 58 , 61 65 ) measured urine NGAL, 14 studies ( 24 , 26 , 30 , 36 38 , 41 , 46 , 49 51 , 54 , 59 , 60 ) measured blood NGAL, and 5 studies ( 19 , 25 , 35 , 40 , 42 ) measured blood and urine simultaneously. The included studies were conducted in 20 countries worldwide, including 11 studies in European countries ( 19 , 20 , 30 , 33 36 , 38 , 54 , 58 , 65 ), 12 studies in the United States ( 10 , 11 , 32 , 40 , 42 , 45 , 49 , 50 , 53 , 61 , 62 , 66 ), 20 studies in Asian countries ( 16 , 18 , 22 , 24 , 25 , 27 29 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, 34 studies ( 10 , 11 , 16 18 , 20 22 , 24 , 27 29 , 31 34 , 39 , 42 45 , 47 , 48 , 52 , 53 , 55 – 58 , 61 65 ) measured urine NGAL, 14 studies ( 24 , 26 , 30 , 36 38 , 41 , 46 , 49 51 , 54 , 59 , 60 ) measured blood NGAL, and 5 studies ( 19 , 25 , 35 , 40 , 42 ) measured blood and urine simultaneously. The included studies were conducted in 20 countries worldwide, including 11 studies in European countries ( 19 , 20 , 30 , 33 36 , 38 , 54 , 58 , 65 ), 12 studies in the United States ( 10 , 11 , 32 , 40 , 42 , 45 , 49 , 50 , 53 , 61 , 62 , 66 ), 20 studies in Asian countries ( 16 , 18 , 22 , 24 , 25 , 27 29 , …”
Section: Resultsmentioning
confidence: 99%
“…The included studies covered various backgrounds of AKI. Among them, 15 studies reported AKI occurred after CPB surgery ( 11 , 19 , 21 , 24 , 33 , 36 , 40 , 42 , 46 , 50 , 53 , 56 , 58 , 65 , 66 ), 12 studies reported AKI occurred in asphyxiated neonates ( 22 , 28 , 30 , 31 , 35 , 37 39 , 47 , 51 , 54 , 57 ), and the remaining 26 studies reported AKI occurred in children hospitalized for a variety of diseases, including sepsis, burns, solid tumors, post-liver transplantation, nephrotoxic drug use, imaging, and preterm, neonatal congenital heart disease, neonatal Hyperbilirubinemia, neonatal general surgery, etc. The diagnostic criteria for AKI used in the original studies varied and were mainly divided into the following three: pediatric risk, injury, failure, loss, final and end stage (PRIFLE) ( 67 ), Acute Kidney Injury Network (AKIN) ( 68 ) and Kidney Disease: Improving Global Outcomes (KDIGO) ( 69 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation